2006
DOI: 10.1093/jhered/esl006
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Sequence Variation in Portuguese Native Dog Breeds: Diversity and Phylogenetic Affinities

Abstract: In an extensive survey of the genetic diversity in Portuguese dogs, we have examined an 887-bp fragment of the mitochondrial DNA (mtDNA) from 8 Portuguese, 1 Spanish, and 2 North African native dog breeds, including village dogs from Portugal and Tunisia. Forty-nine haplotypes were found in the 164 individuals analyzed, with private haplotypes being found in several breeds. For example, the Castro Laboreiro Watchdog, a rare breed from a small and isolated region in Portugal, was monomorphic for mtDNA and posse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 47 publications
4
32
0
1
Order By: Relevance
“…S6), the clades that are believed to contain Ͼ95% of domestic dogs (6). Over the region sequenced in (6) and ignoring indels, we found 18 African haplotypes that were not described by (6); 14 in A clade [one of which was found in Africa by (10)], one in B clade, and three in C clade. The Puerto Rican and United States mixed-breed dogs had 8 A clade and one B clade haplotypes (only one haplotype, a Puerto Rican A clade haplotype, ws not previously described in ref.…”
Section: Inference Of Populationmentioning
confidence: 86%
See 1 more Smart Citation
“…S6), the clades that are believed to contain Ͼ95% of domestic dogs (6). Over the region sequenced in (6) and ignoring indels, we found 18 African haplotypes that were not described by (6); 14 in A clade [one of which was found in Africa by (10)], one in B clade, and three in C clade. The Puerto Rican and United States mixed-breed dogs had 8 A clade and one B clade haplotypes (only one haplotype, a Puerto Rican A clade haplotype, ws not previously described in ref.…”
Section: Inference Of Populationmentioning
confidence: 86%
“…Their results confirmed previous mtDNA evidence of dog domestication from Eurasian wolves (5), showed that East Asian dogs had the highest mtDNA diversity of any region, suggesting an East Asian origin of domestication. However, subsequent work by Pires et al (10) has shown that mtDNA does not show significant population structure in village dogs. Because Savolainen et al included many East Asian village dogs but few village dogs from other regions, their conclusion of high levels of East Asian diversity is likely a consequence of high levels of mitochondrial diversity in village dogs and not necessarily an indication of East Asian domestication.…”
mentioning
confidence: 96%
“…The mtDNA sequence of the African dog specimen belongs to clade A, which is nowadays the most common lineage found in dogs worldwide, including North Africa (Boyko et al, 2009) and Iberia (Pires et al, 2006). Here we contribute only one sample from Thamusida: interestingly, it shared a clade A haplotype with three other samples from Lugo.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of dog clades was undertaken through comparison with reference sequence data of extant Iberian dogs and wolves trimmed to the 181 base pairs fragment. Detry and Cardoso, 2010) reference sequence data on extant dogs from Iberia and North Africa, and comprising breed and village dogs from 1) Pires et al (2006), 49 haplotypes, 887 base pair long with GenBank accession numbers AY706476eAY706524 (Pires et al, 2006); and 2) Pang et al (2009), haplotypes A4, A5, A10, A11, A19, A20, A22, A33, A34, A127, B1, D6, D7 (Pang et al, 2009). An alignment of all these sequences/haplotypes is available from Partial_MtDNA_SequenceAlignment_DOG__Roman_QInt (fasta).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
See 1 more Smart Citation